Extending MIEZE spectroscopy towards thermal wavelengths. Issue 6 (27th October 2022) - Jochum, Johanna K.; Franz, Christian; Keller, Thomas; Pfleiderer, Christian
Abstract : A modulation of intensity with zero effort (MIEZE) setup is proposed for high‐resolution neutron spectroscopy at momentum transfers up to 3 Å −1, energy transfers up to 20 meV and an energy resolution in the microelectronvolt range using both thermal and cold neutrons. Abstract : A modulation of intensity with zero effort (MIEZE) setup is proposed for high‐resolution neutron spectroscopy at momentum transfers up to 3 Å −1, energy transfers up to 20 meV and an energy resolution in the microelectronvolt range using both thermal and cold neutrons. MIEZE has two prominent advantages compared with classical neutron spin echo. The first is the possibility to investigate spin‐depolarizing samples or samples in strong magnetic fields without loss of signal amplitude and intensity. This allows for the study of spin fluctuations in ferromagnets, and facilitates the study of samples with strong spin‐incoherent scattering. The second advantage is that multi‐analyzer setups can be implemented with comparatively little effort. The use of thermal neutrons increases the range of validity of the spin‐echo approximation towards shorter spin‐echo times. In turn, the thermal MIEZE option for greater ranges (TIGER) closes the gap between classical neutron spin‐echo spectroscopy and conventional high‐resolution neutron spectroscopy techniques such as triple‐axis, time‐of‐flight and back‐scattering. To illustrate the feasibility of TIGER, this paper presents the details of its implementation at the RESEDA beamline at FRM II by means of an additional velocity selector, polarizer and analyzer.